Development of a new expanded next‐generation sequencing panel for genetic diseases involved in dyslipidemia. Issue 6 (4th September 2020) - Marmontel, Oriane; Rollat‐Farnier, Pierre Antoine; Wozny, Anne‐Sophie; Charrière, Sybil; Vanhoye, Xavier; Simonet, Thomas; Chatron, Nicolas; Collin‐Chavagnac, Delphine; Nony, Séverine; Dumont, Sabrina; Mahl, Muriel; Jacobs, Chantal; et al.
Abstract: The aim of this study was to provide an efficient tool: reliable, able to increase the molecular diagnosis performance, to facilitate the detection of copy number variants (CNV), to assess genetic risk scores (wGRS) and to offer the opportunity to explore candidate genes. Custom SeqCap EZ libraries, NextSeq500 sequencing and a homemade pipeline enable the analysis of 311 dyslipidemia‐related genes. In the training group (48 DNA from patients with a well‐established molecular diagnosis), this next‐generation sequencing (NGS) workflow showed an analytical sensitivity >99% (n = 532 variants) without any false negative including a partial deletion of one exon. In the prospective group, from 25 DNA from patients without prior molecular analyses, 18 rare variants were identified in the first intention panel genes, allowing the diagnosis of monogenic dyslipidemia in 11 patients. In six other patients, the analysis of minor genes and wGRS determination provided a hypothesis to explain the dyslipidemia. Remaining data from the whole NGS workflow identified four patients with potentially deleterious variants. This NGS process gives a major opportunity to accede to an enhanced understanding of the genetic of dyslipidemia by simultaneous assessment of multiple genetic determinants. Abstract :